Sum of Sequence of Squares/Proof by Binomial Coefficients

From ProofWiki
Jump to navigation Jump to search

Theorem

$\displaystyle \forall n \in \N: \sum_{i \mathop = 1}^n i^2 = \frac {n \paren {n + 1} \paren {2 n + 1} } 6$


Proof

From Binomial Coefficient with One:

$\dbinom n 1 = n$

From Binomial Coefficient with Two:

$\dbinom n 2 = \dfrac {n \paren {n - 1} } 2$


Thus:

\(\ds 2 \binom n 2 + \binom n 1\) \(=\) \(\ds 2 \dfrac {n \paren {n - 1} } 2 + n\)
\(\ds \) \(=\) \(\ds n \paren {n - 1} + n\)
\(\ds \) \(=\) \(\ds n^2\)

Hence:

\(\ds \sum_{i \mathop = 1}^n i^2\) \(=\) \(\ds \sum_{i \mathop = 1}^n \paren {2 \binom i 2 + \binom i 1}\)
\(\ds \) \(=\) \(\ds 2 \binom {n + 1} 3 + \binom {n + 1} 2\) Sum of Binomial Coefficients over Upper Index
\(\ds \) \(=\) \(\ds \frac {2 \paren {n + 1} n \paren {n - 1} } {3 \times 2 \times 1} + \frac {\paren {n + 1} n} 2\) Definition of Binomial Coefficient
\(\ds \) \(=\) \(\ds \frac {n \paren {n + 1} \paren {2 n + 1} } 6\) after algebra

$\blacksquare$


Also see

Sources